Penerapan Kegiatan Menceritakan Kembali Isi Cerita Untuk Meningkatkan Keterampilan Berbicara Anak di TK Melati Indah - Joni Joni; Melvi Lesmana Alim; Eri Yanti; Darmanina Lisanti (Jurnal Pendidikan Tuntas, 2023)
This study aims to enhance early childhood speaking skills at TK Melati Indah through the implementation of the story-retelling method. This research employs Classroom Action Research (CAR) using the Kemmis and McTaggart model, involving 17 children aged 4-5 years over two cycles. Data were collected through observation and documentation, then analyzed using quantitative and qualitative data analysis techniques. The results indicate an improvement in children's speaking skills, with an average percentage reaching 55.01% in cycle I and increasing to 76.81% in cycle II. Thus, the story-retelling method has proven effective in enhancing the speaking skills of early childhood learners.